Implikasi Hukum Peluncuran Satelit oleh Swasta Dalam Kerangka Hukum Internasional - Triadi, Irwan; Faidzuddin, Achmad (Media Hukum Indonesia (MHI), 2025)
In recent years, satellite launch activities by the private sector have increased significantly, especially by global companies such as SpaceX, OneWeb, and Amazon. This phenomenon marks a shift in the dominance of space exploration from states to private entities. However, this development raises complex legal issues, especially related to the principle of international responsibility as stipulated in the Outer Space Treaty 1967 and the Liability Convention 1972. This study aims to examine the legal implications arising from losses due to satellite launches by the private sector against states and third parties, and to analyze the effectiveness of the launching state's supervision in the context of international and national law. The Normative-Qualitative Approach to Satellite Launch Law is an analytical method used to understand and analyze the legal aspects of satellite launches. Through, this study found that although the launching state still bears absolute and fault-based responsibility for the activities of non-state entities, the oversight and law enforcement mechanisms are still weak and not yet adaptive to the development of the commercial space industry. The absence of strict sanctions, regulatory gaps, and limited international jurisdiction make the principle of international responsibility difficult to apply optimally. Therefore, it is necessary to update the legal framework, increase national capacity, and international cooperation to create fair, responsible, and sustainable space governance.